Education Is Ceremony: Thinking With Stories of Indigenous Youth and Families (LEARNing Landscapes, 2018)
This research with three Indigenous youth and their families is an intergenerational narrative inquiry around experiences of belonging and identity making. Pulling forward teachings from Indigenous Elder Francis Whiskeyjack, a metaphor of “education as ceremony” is juxtaposed with the ceremonies of “schooling” (Greene, 2001). Thinking with stories lived and told by the youth and their families, I retell stories as a teacher, mother, and now, teacher educator. Experiencing personal and practical shifts to my teaching and learning, I reconsider the ceremonies of “schooling.” This study offers possibilities for how educators might co-compose more relational and educative (Dewey, 1938) experiences in schools.
Keywords: narrative inquiry; urban Indigenous youth and families; teacher education; belonging and identity making; ceremonies